Gap analysis comparing protected areas with potential natural vegetation in Tuscany (Italy) and a GIS procedure to bridge the gaps. (2nd January 2016) - Viciani, D.; Lastrucci, L.; Geri, F.; Foggi, B.
Abstract : The aim was to compare the protected area (PA) network in Tuscany, Italy, with the areas referenced to different types of potential natural vegetation (PNV), to determine whether they are adequately represented for plant and habitat conservation purposes. For PNV, an existing but slightly updated and modified Italian Vegetation Series (VS) map was used. Each VS type corresponds to vegetation complexes that live under homogeneous environmental conditions and can each be considered an ecological land unit at the working scale employed here. Using GIS techniques, the geographic layers of PAs and VS were processed with spatial intersection to extract and quantify the VS contained within the boundaries of PAs. As a minimum conservation goal, we used the widely accepted 10% target threshold. It was found that, even though Tuscan PAs covered almost 20% of the total land surface, 94% of VS types resulted to be included in PAs with a percentage of at least 10% of their total area. The survey shows that the VS with the higher degree of inclusion in PAs are distributed in the Mediterranean Tuscany (coast and Tuscan Archipelago) and in some inner areas such as Apuan region, northern Apennines, Amiata Mt. and Farma-Merse Valley. Two VS types must be considered under-protected (i.e. contained in an existing PA network with percentages < 10%). We propose a simple GIS procedure based on certain priority assumptions: (a) existing PAs should be enlarged rather than new ones created and (b) their naturalness taken into account. This procedure produces a suitability map useful for identifying the best areas in which a local administration might look for solutions to bridge the gaps.